Development of new reactions and reagents in carbene-catalyzed addition of carbon and nitrogen nucleophiles to unsaturated acyl azolium intermediates - Wu, Xingxing (2017)
This thesis focuses on development of efficient protocols for access to advanced complex molecules enabled by N-heterocyclic carbene (NHC) catalyzed LUMO activation of enal or its ester derivatives, and discovery of polyhalide as simple organic oxidant for oxidative carbene catalysis. It contains five parts: Chapter 1 first gives a brief introduction to the history of asymmetric organocatalysis, followed by development of N-heterocyclic carbene (NHC) catalysis. This includes three main aspects, (a) catalysis involving umpolung acyl-anion, (b) homoenolate catalysis, (c) reactions involving acyl azolium intermediates. This chapter also illustrates the challenges and opportunities in NHC catalyzed reactions, especially in heteroatoms as nucleophiles for α, β-unsaturated acyl azolium and simple oxidants for oxidative NHC catalysis. Chapter 2 describes a single-step, organocatalytic and enantioselective cascade process for access to a multi-cyclic lactone that constitutes the core structure of iridoids. This protocol shows the synthetic power of a NHC catalyst for the activation of a readily available and stable carboxylic ester to give the unsaturated acyl azolium intermediate. Chapter 3 demonstrates an efficient protocol for the preparation of pyrazolidinone products via nucleophilic β-carbon amination of enals under oxidative NHC catalysis. The heterocycle adducts from the catalytic reaction can readily undergo further transformations to afford various useful functional molecules, such as pyrazolidines and β-amino acid derivatives. Chapter 4 shows a novel and efficient cascade approach for the direct assembly of two privileged scaffolds (pyrrolidine and β-lactone) with good to excellent yield and enantioselectivity. This study sheds light on modulating the reactivity of nitrogen atom for challenging NHC-catalyzed asymmetric C-N bond formations. Chapter 5 introduces polyhalide reagents as simple and inexpensive oxidants for oxidative NHC catalysis, providing efficient methods for functionalization of the α, β and γ atoms of aldehydes. The oxidative process involves multiple radical intermediates, and shall inspire new reaction development via NHC-catalyzed radical process.